Gastropods from the Late Jurassic–Early Cretaceous seep deposits in Spitsbergen, Svalbard - Kaim, Andrzej; Hryniewicz, Krzysztof; Little, Crispin T. S.; Nakrem, Hans Arne (Zootaxa, 2017)
Eleven gastropod species from seven latest Jurassic–earliest Cretaceous hydrocarbon seep deposits from central Spitsbergen, Svalbard are described and illustrated. Six new species and one new genus are introduced. Sassenfjordia gen. nov. is tentatively classified as a naticoid and is characterized by a naticiform gross teleoconch morphology and a large protoconch ornamented with spiral ribs, similar to those present in the subfamily Sininae. The patellogastropod ?Pectinodonta borealis sp. nov. represents the oldest occurrence of pectinodontid limpets in chemosynthesis-based associations. The colloniid Hikidea svalbardensis sp. nov. is the oldest confirmed occurrence of this genus so far. The eucyclid Eucycloidea bitneri sp. nov. is the second report of an occurrence of this genus at hydrocarbon seeps (both of which come from the Paleo-Barents Sea). Abyssomelania sp. is the third known, and the oldest occurrence of this genus. Hudlestoniella hammeri sp. nov. represents another occurrence of this genus at seeps in the Paleo-Barents Sea; its current higher-rank assignment is reviewed herein. It may belong either to the rissoids, as previously suggested, or to the abyssochrysoids (or zygopleurids). A fossil identified as Cretadmete sp. is here classified in the Purpurinidae, a family of stem neogastropods or tonnoideans. The heterobranch Hyalogyrina knorringfjelletensis sp. nov. is the oldest occurrence of hyalogyrinids in chemosynthesis-based associations. Several oldest occurrences of seep taxa in moderately shallow-water seeps in Spitsbergen suggest that the previously questioned onshore-offshore hypothesis of seep and vent colonization should be carefully re-investigated.